A new technique to improve the machinability of hardened steel AISI H13 in end milling - Amin, A. K. M. Nurul; Mokhtar, Suhaily; Patwari, Muhammed Anayet Ullah; Abdul Razak, Nurhayati (2010)
Hardened materials like AISI H13 steel are generally regarded as difficult to cut materials because of their high hardness due to high carbon content, which however allows them to be used extensively as the hot working tools like, dies and moulds. The challenges in machining this steel in hardened state led to many research works dedicated towards enhancing its machinability. In this work, preheating technique has been used to improve machinability of the material under different cutting conditions...